Do Tar Roads Bring Tourism? Growth Corridor Policy and Tourism Development in the Zambezi region, Namibia - Linus Kalvelage; Javier Revilla Diez; Michael Bollig (The European Journal of Development Research, 2021)
There are high aspirations to foster growth in Namibia's Zambezi region via the development of tourism. The Zambezi region is a core element of the Kavango-Zambezi Transfrontier Conservation Area (KAZA), a mosaic of areas with varying degrees of protection, which is designed to combine nature conservation and rural development. These conservation areas serve as a resource base for wildlife tourism, and growth corridor policy aims to integrate the region into tourism global production networks (GPNs) by means of infrastructure development. Despite the increasing popularity of growth corridors, little is known about the effectiveness of this development strategy at local level. The mixed-methods approach suggests a link between a tandem of infrastructure development and tourism-oriented policies on the one hand, and increased value creation from tourism in the region on the other hand. Yet, the promises of tourism-driven development reach only a very limited number of rural residents.
Keywords: 330; Growth corridor; Tourism GPN; Hunting tourism; CBNRM; KAZA; Zambezi region